The Influence of Workload, Burnout, and Interpersonal Communication on Employee Performance in the Terminal Operations Division of PT Berlian Jasa Terminal Indonesia - Zukmarini, Shabila Dhania; Rini, Hesty Prima (Management Science Research Journal, 2025)
The growth of the service industry is highly dependent on the quality of human resources, as they serve as strategic assets in achieving effective and optimal performance. To support organizational goals, service companies must foster a conducive work environment. This study examines the effects of workload, burnout, and interpersonal communication on employee performance in the Operations Division of PT Berlian Jasa Terminal Indonesia. Using a quantitative approach with saturated sampling of 50 employees, data were collected through questionnaires and analyzed with Partial Least Square Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results show that workload and burnout have negative and significant effects on performance, while interpersonal communication has a positive and significant effect. This indicates that effective workload management, prevention of burnout, and the enhancement of interpersonal communication play a significant role in optimizing employee performance within the operational environment of Berlian Terminal, which requires intensive coordination and consistent port service delivery.